Interference in the processing of adjunct control - Parker, Dan; Lago, Sol; Phillips, Colin (Frontiers in Psychology, 2015)
Recent research on the memory operations used in language comprehension has revealed a selective profile of interference effects during memory retrieval. Dependencies such as subject-verb agreement show strong facilitatory interference effects from structurally inappropriate but feature-matching distractors, leading to illusions of grammaticality (Dillon, Mishler, Sloggett, & Phillips, 2013; Pearlmutter, Garnsey, & Bock, 1999; Wagers, Lau, & Phillips, 2009). In contrast, dependencies involving reflexive anaphors are generally immune to interference effects (Dillon et al., 2013; Sturt, 2003; Xiang, Dillon, & Phillips, 2009). This contrast has led to the proposal that all anaphors that are subject to structural constraints are immune to facilitatory interference. Here we use an animacy manipulation to examine whether adjunct control dependencies, which involve an interpreted anaphoric relation between a null subject and its licensor, are also immune to facilitatory interference effects. Our results show reliable facilitatory interference in the processing of adjunct control dependencies, which challenges the generalization that anaphoric dependencies as a class are immune to such effects. To account for the contrast between adjunct control and reflexive dependencies, we suggest that variability within anaphora could reflect either an inherent primacy of animacy cues in retrieval processes, or differential degrees of match between potential licensors and the retrieval probe.